"Better than having no evaluation done": a pilot project to conduct remote asylum evaluations for clients in a migrant encampment in Mexico - Ranit Mishori; Kathryn Hampton; Hajar Habbach; Elsa Raker; Anjali Niyogi; Dona Murphey (BMC, 2021)
Abstract Background Asylum evaluations are highly specialized medico-legal encounters to collect physical or mental health evidence for use in immigration proceedings. Although the field of asylum medicine is growing, access to these evaluations is still inadequate, particularly for those in United States immigration detention or other forms of custody, such as under the U.S. Migrant Protection Protocols or "Remain in Mexico" policy. Given advances in telehealth in recent years and growing evidence of similar outcomes with in-person management, it seems prudent to examine whether remote modalities may also be effective for conducting mental health asylum evaluations in hard-to-reach populations. Methods We analyzed the responses of 12 U.S. clinicians who conducted 25 cross-border remote mental health evaluations with clients in Mexico prior to the COVID-19 pandemic, and completed a post-evaluation survey regarding their impressions and experiences of the remote encounter. Data were coded through a process of thematic analysis. Results The average evaluation time was 2.3 h, slightly shorter than might be expected from an in-person encounter. Five themes emerged from the coding process: rapport building, achieving overall goal, comparison of in-person vs. remote, technical issues, and coordination. Clinicians encountered a number of challenges including technical difficulties and a decreased ability to establish rapport. Nearly uniformly, however, clinicians noted that despite difficulties, they were able achieve the goals of the evaluation, including rapport building and diagnosis. Conclusion Remote evaluations appear to achieve their intended goal and may be useful in expanding legal options for hard-to-reach asylum seekers.